Effects of sake lees intake on fecal uremic toxins, plasma D-alanine, constipation, and gut microbiome in healthy adults: A single-arm clinical trial - Toshiaki Tokumaru; Tadashi Toyama; Yusuke Nakade; Hisayuki Ogura; Megumi Oshima; Shiori Nakagawa; Masashi Mita; Taro Miyagawa; Shinji Kitajima; Akinori Hara; Norihiko Sakai; Miho Shimizu; et al. (PLoS ONE, 2025)
Background Sake lees consumption has the potential to reduce uremic toxins by influencing the gut microbiome. To lay the groundwork for a clinical trial targeting chronic kidney disease (CKD) patients, we conducted a pilot study to explore the relationship between sake lees intake and changes in fecal uremic toxin levels among individuals with constipation. D-alanine, a renoprotective component of sake lees, was also evaluated. Methods This single-arm, before and after study lacked a control group. Participants met the diagnostic criteria for chronic constipation. They consumed 25 or 50 g of sake lees daily for 6 weeks. The primary endpoint was the change in fecal indole levels from baseline. Secondary endpoints included changes in plasma D-alanine, Constipation Scoring System (CSS) scores, and the composition of the fecal microbiome. Results Eight participants, with a mean age of 46 years, completed the study. Percentage changes in fecal indole levels were +42%, + 52%, and −6% at weeks 2, 4, and 6, respectively. Plasma D-alanine levels showed percentage changes of +39%, + 24%, and +38% at the same time points. CSS scores improved from 9.2 to 6.8 by week 2 and remained stable after week 4. The proportion of the phylum Firmicutes in the gut microbiome increased slightly from 53% at baseline to 57% by week 6. Conclusion Sake lees intake may reduce fecal uremic toxins, elevate plasma D-alanine levels, alleviate constipation, and modify the gut microbiome. However, future studies are needed to confirm these effects in patients with CKD.